A comparative interventional study on the efficacy of single and multiple dose combination drug regimen of leucorrhea among women in reproductive age group - K., Sivakumar; S., Ajay Raj; K., Sujatha (International Journal Of Community Medicine And Public Health, 2017)
Background: Reproductive tract infections (RTIs) in women are becoming major public health problem not only in India but also over the world. Syndromic approach is advocated by World Health Organization (WHO) to manage common RTIs using clinical flow charts based on identifying a syndrome that cause the symptoms reported by patients. The most commonly reported among the women with RTIs is abnormal vaginal discharge or Leucorrhea. Single dose regimen is not preventing the recurrence of infections. A second course of treatment is required followed by standard single dose regimen for achieving better cure rate in chronic vaginal discharge. Objective of the study was to compare the efficacy of single dose drug combination regimen with multiple dose regimens in the treatment of leucorrhoea. Methods: Quasi-experimental study was done in Urban field service area, RMMCH – Chidambaram among Married women in the reproductive age group (15-49 years) with complaints of abnormal vaginal discharge for ≥15 days coupled with any one of the symptoms suggestive of RTI. The study subjects were categorized into two groups – one with single dose regimen and the other with multiple dose regimen. Follow up was done on day 7, 15 and after 6 months of therapy. Results: A total of 113 subjects were recruited with 57 participants in single dose group and 56 in multiple dose groups. The subjects who received single dose had a better cure rate as compared to multiple dose group on day 7(87.7% & 85.7%), day 15 (94.7% & 89.3%) and after six months (84.2% & 76.8%) assessment respectively. Recurrence rate was found to be equal in both the groups. Our study indicates that variables such as age of the study subjects and type of flow had significant association with the outcome. Conclusions: Single-dose therapy is as effective as multiple- dose in the management of vaginal discharge based solely on symptoms. The multiple drug regimens can be given if the symptoms persist after single drug regimen as the chances of developing complications due to chronic vaginal discharge are high.